Etiology and significance of incidentally detected focal colonic uptake on FDG PET/CT - Purandare, Nilendu C; Gawade, Sachin K; Puranik, Ameya D; Agrawal, Archi; Shah, Sneha; Rangarajan, Venkatesh (Indian Journal of Radiology and Imaging, 2012)
Background: Incidental colonic uptake of 18F-flurodeoxyglucose (FDG) is not an infrequent finding encountered during whole body positron emission tomography (PET) imaging. Almost all studies on this topic are in Western populations, which have a markedly different epidemiological profile for colorectal premalignant and malignant conditions as compared to that of the Indian subcontinent. Aim: The purpose of this study was to assess the etiology of incidentally detected focal FDG uptake in the colon by comparing it with colonoscopy and histopathology. Materials and Methods: Electronic medical records of patients who underwent FDG PET/computed tomography (CT) at our institution for a 2½-year period from January 2009 to July 2011 were reviewed. There were 32 out of 9000 (0.35%) patients whose PET/CT reports mentioned incidental focal colonic FDG uptake, of which 24 patients subsequently underwent colonoscopy. Lesions which appeared neoplastic on colonoscopy were confirmed with histopathology obtained after biopsy or surgery. Colonoscopy and pathology findings were considered as gold standard. Results: Among the 24 patients who underwent a colonoscopy, 3 patients had normal findings (12.5%). A positive colonoscopy was noted in 21 patients (87.5%) with the lesion coinciding with the location described in the PET/CT report. Adenomatous polyps were detected in 12 patients (37.5%), whereas in 8 patients (25%) malignant lesions were confirmed [adenocarcinoma n = 5, non-Hodgkin′s lymphoma (NHL) n = 2, malignant melanoma n = 1]. In one patient, colonic uptake was diagnosed as inflammatory. The mean standardized uptake value max (SUV max ) for the 12 premalignant lesions was 16.9 ± 9.6 (range 7.5-37.4) and the mean SUV max for the 8 malignant lesions was 12.9 ± 5.5 (range 6.7-21.6). The difference in SUV max between the premalignant adenomatous polyps and the malignant lesions was not statistically significant (P = 0.316). Conclusions: Our study shows that a significant proportion of patients (62.5%, 20/32) showing an incidental focal FDG uptake will harbor premalignant (adenomatous polyps) or malignant lesions, and further evaluation with colonoscopy and biopsy is warranted in such cases.
Keywords: 18F-flurodeoxyglucose; positron emission tomography; colon cancer; colonoscopy; incidental colonic lesions; polyps